Protozoa Parasitik pada Ikan Sidat (Anguilla spp.) Asal Danau Lindu, Sulawesi Tengah - Arif Rahman Jabal; Umi Cahyaningsih; Risa Tiuria (Institut Pertanian Bogor, 2015)
Infection protozoan parasitic on eels (Anguilla spp.) from Lindu Lake was affected weight eels and health eels. The protozoan parasitic examinations were collection of eels, inspection eels, observation, measurement, identification of parasites, and staining protozoan used giemsa stained, trematode used semichons’s acetocarmine stained and nematode used clove oil and KOH. The diversity of parasitic protozoan found such as: Myxidium sp., Myxobolus sp., Chilodonella sp., Ceratomyxa sp., Balantidium sp., Henneguya sp., and Glugea sp. The highest prevalence Myxidium sp. in eels was 77% and no protozoan dominated between other parasites. Based on chi-square test, protozoan parasitic had a different preference to organs of eels.